Peran Kader Posyandu dalam Pencegahan dan Deteksi Dini TB pada Ibu dan Anak di Puskesmas Siriwini - Anisa N.Sulistiyowati; Umratun Hayati; Oktofina Rumaropen; Fero Delvina Mona Iyowau; Rosalin Marice Korano (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Posyandu (Integrated Health Service Post) is a community-based initiative that supports health development, including the prevention and control of tuberculosis (TB), particularly among vulnerable groups such as mothers and children. This community service program aims to enhance the capacity of Posyandu cadres in the early detection and prevention of TB through a series of activities, including health education sessions, the distribution of pocketbooks, and training in the use of flipcharts. The program was implemented in the working area of Puskesmas Siriwini, Nabire Regency, involving five Posyandu units and 18 active cadres. The implementation method employed a participatory and interactive approach to improve cadres' understanding and skills in identifying TB symptoms and effectively delivering health information to the community. Evaluation results showed a 20% increase in cadres' knowledge based on pre- and post-test assessments. Education-based interventions and the use of visual aids proved effective in strengthening the role of cadres as agents of change within the community, particularly in detecting TB symptoms, providing public education, and breaking the chain of transmission. These findings highlight the importance of empowering Posyandu cadres through continuous training and the need for cross-sectoral support to improve the effectiveness of TB control programs, especially among mothers and children.